Entrepreneurship in Jordan: The eco-system of the Social Entrepreneurship Support Organizations (SESOs) - Amani Jarrar (Journal of Innovation and Entrepreneurship, 2022)
This study aims at assessing the Social Entrepreneurship Support Organizations (SESOs) in Jordan with an updated eco-system reflecting the better resourced Social Entrepreneurship eco-system characterized with comprehensive information; covering the stakeholders' identification data, ongoing projects and initiatives, work scope, and their targeted groups, accurate data based on a well-developed survey and analysis of the survey data by the authors' experience in this filed. This study also aims at assessing the SESOs capacity by coincide their desired needs and their actual needs and limit the social innovation concept variation among the different institutions in the ecosystem. This study also provides a survey analysis for the Social Entrepreneurship Support Organizations (SESOs); as an attempt to identify their characteristics and roles in Jordan by adopting the methodology of qualitative and quantitative analysis approach. Results show that (57.89%) of the SESO's in Jordan have dedicated programs that focus on women's inclusion, and that (68.42%) are hiring more than 50% in their staff. Besides that, results also show that (59.65%) of the SESO's in Jordan did not dedicate programs for people with disabilities (PWD); which is a high portion in neglecting this segment of people. Besides that (54.39%) do not have designed facilities friendly using for people with disabilities. Moreover, results show that (73.68%) had dedicated programs for youth with different age groups, and (77.19%) of the SESO's in Jordan had attempted to identify, understand, and actively removing barriers that exist for certain groups of young people in society. Moreover, (70.18%) of the SESO's in Jordan had organized specific outreach mechanisms to identify, meet, engage, and/or serve different population groups. Finally, results show that (38.60%) of the SESO's in Jordan had dedicated programs for refugees.
Keywords: 650; Eco-system; Entrepreneurship; Jordan; Social entrepreneurship